KOVAC'S DILEMMA - García, Jean Pierre (2020)
Agency Theory is a central issue in the field of Corporate Finance and analyzes the relationship between investors and those who are responsible for managing their investments, the agents. This theory has received frequent criticism for not incorporating, within its analysis, considerations or recommendations about ethical behavior in people's decisions. This article reflects on the importance of morality and ethics in society.